Opiate use disorders and overdose: Medical students' experiences, satisfaction with learning, and attitudes toward community naloxone provision. (November 2018) - Tobin, H.; Klimas, J.; Barry, T.; Egan, M.; Bury, G.
Abstract: Introduction: Opiate use disorder is a common condition in healthcare services in Ireland, where over 200 opiate overdose deaths occur annually. There is limited addiction medicine education at undergraduate level and medical graduates may not be adequately prepared to diagnose and manage opioid use disorders and emergency drug overdose presentations. Therefore, we examined final-year medical students' learning experiences and attitudes toward opioid use disorder, overdose and community naloxone provision as an emerging overdose treatment. Methods: We administered an anonymous paper-based survey to 243 undergraduate medical students undertaking their final professional completion module prior to graduation from University College Dublin, Ireland. Results were compared with parallel surveys of General Practitioners (GPs) and GP trainees. Results: A total of 197 (82.1%) completed the survey. Just under half were male, and most were aged under 25 (63.3%) and of Irish nationality (76.7%). The students felt moderately prepared to recognise opioid use disorder, but felt less prepared to manage other aspects of its care. Most had taken a history from a patient with an opioid use disorder (82.8%), and a third had witnessed at least one opioid overdose. Although 10.3% had seen naloxone administered, most had never administered naloxone themselves (98.5%). Half supported wider naloxone availability; this was lower than support rates among GPs (63.6%) and GP trainees (66.1%). Conclusions: Our findings suggest an unmet learning need in undergraduate training on opioid use disorder, with potential consequences for patient care. Highlights: Most students had taken a history from a patient with an opioid use disorder and a third had witnessed an opioid overdose. Over half supported wider naloxone availability and its lay distribution to address Ireland's overdose problem. Few students had direct experience of overdose management although many had been exposed to patients using opiates. High student exposure to patients using opiates presents an opportunity to increase addiction content in medical curricula.